Case Report: Neuropsychological Findings in IgLON5 Antibody Disorder - El Shazly, Jasmin; Juenemann, Martin; Gerriets, Tibo; Tschernatsch, Marlene (Frontiers in Neurology, 2021)
IgLON5 antibody encephalopathy is a rare but increasingly recognized disorder with a variety of clinical signs. Typical symptoms are sleep disorder, gait disturbances, signs of bulbar dysfunction and a variety of neurological symptoms like oculomotor abnormalities and movement disorders. In addition, cognitive decline can be a prominent symptom. So far, there are only a few studies that have dealt with the course and possible treatment options of IgLON5 antibody encephalopathy. In this study the clinical case of a female patient with IgLON5 antibody disease and the response to treatment is described. Here we report on the case of a 67-year-old female patient who showed cognitive deterioration, gait difficulties, and chronic obstructive sleep disorder. The diagnostic course showed a positive anti-IgLON5 serum and anti-IgLON5 IgG antibodies in cerebrospinal fluid. The patient was subsequently treated with high dosage i.v. methylprednisolone, i.v. immunoglobulins and plasmapheresis. Neuropsychological tests showed cognitive deficits in different domains, including verbal and visual memory. Both, neuropsychological deficits and antibody titer, showed an improvement after plasmapheresis. The presented case shows that IgLON5 disease can present with rapidly progressing cognitive deterioration as the prominent symptom, adding to the variety of clinical signs in this disorder. Testing for IgLON5-antibodies should be considered in patients with progressing cognitive decline, especially if accompanied by sleep disorders or neurological symptoms like oculomotor abnormalities, dysautonomia or bulbar signs.